Utilization of genetic resources in a country center of origin: The case of cocoa in Peru - Pastor-Soplin, Santiago H. (2022)
The Peruvian production of cocoa represents, approximately, 2% of the world production, with a very recognized contribution because of the quality and diversity of its flavors and aromas. With a millenary Amazonian origin and proved utilization by at least 5200 years ago, this crop just became visible for the agrarian development in the last two decades, when it was used with relative success for the substitution of illegal coca crops ¿And how much is the academy contributing to the value chain of cocoa? A sample of 44 theses which cocoa obtained from production centers and farmers plots was their object of study, has been registered and analyzed in an exploratory way. 41 theses were for obtain professional titles, two for magister degree and one for doctorate degree. These theses were done in universities of 13 Department of Peru, where Lima reached the highest number (12). Eleven theses addressed germplasm research activities aimed to cocoa transformation and/or innovation, thus conferring added value with potential commercial use. The researches were related to four productive sectors with a clear potential in the global market of genetic resources. In any case, the researches were done under the legal certainty of the system of access to genetic resources and fair and equitable benefit-sharing of the Nagoya Protocol.